Social status strategy in early adolescent girls: Testosterone and value-based decision making. (July 2017) - Cardoos, Stephanie L.; Ballonoff Suleiman, Ahna; Johnson, Megan; van den Bos, Wouter; Hinshaw, Stephen P.; Dahl, Ronald E.
Highlights: Increases in testosterone predict an increased appetite for social admiration. Risk taking early adolescence is associated with changes in testosterone. Higher testosterone predicted prioritization of social status over financial gain. Abstract: There has been strong interest, spanning several disciplines, in understanding adolescence as a developmental period of increased risk-taking behavior. Our goals focus on one line of investigation within this larger developmental risk framework. Specifically, we examined levels of pubertal hormones in girls in relation to their willingness to take greater financial risks to gain social status. To this end, we tested the hypothesis that higher levels of testosterone during the ages of pubertal maturation are associated with a greater willingness to sacrifice money for social admiration. Sixty-three girls ages 10–14 ( Mage  = 12.74) participated in laboratory measures and completed at-home saliva sample collection. The Pubertal Development Scale (PDS) and basal hormone levels (testosterone, estradiol, DHEA) measured pubertal maturation. We made use of a developmentally appropriate version of an Auction Task in which adolescents could take financial risks in order to gain socially motivated outcomes (social status). PDS and testosterone were each associated with overall levels of financial risk taking over the course of the Auction Task. In hierarchical models, PDS and testosterone were predictors of the slope of overbidding over the course of the task. Results provide evidence for the role of testosterone and pubertal maturation in girls' motivations to engage in costly decision making in order to gain social status. Findings contribute to our understanding of the developmental underpinnings of some interesting aspects of adolescent risk behavior.